Properties of self compacting concrete containing unground palm oil fuel ash as partial sand replacement - Ali, Alaa Yousif (2014)
Since last few years replacement concrete materials with industrial by-products and agricultural wastes in concrete production are widely used. It imparts positive environmental effect because the waste materials are not released to the environment. Malaysia is well known as the main crude palm oil producer and exporter in the world. Million tons of agro wastes such as palm oil fuel ash (POFA) are being produced every year with no commercial return on it. Due to the pozzolanic behaviour possessed by POFA, it could be significant when the POFA is being recycled and used in production of concrete. This project report presents part of the on-going research project to study the effects of unground Palm Oil Fuel Ash (UPOFA) as a sand replacement (the size between 2.36 mm to 600 µm) on the properties of self-compacting concrete in terms of compressive, flexural, splitting tensile strength, workability, absorption and density. The testing takes two stages, the first stage depended on five different concrete mixes were prepared, the different amount from UPOFA as a sand replacement were used in each concrete mix. i) 0% UPOFA as control mix, ii) 25% UPOFA, iii) 35% UPOFA, iv) 45% UPOFA, v) 100% UPOFA. The result indicates that a 25% replacement gave better workability and strength at curing periods at (7, 28, 56, 90) days. The 25% mix was then selected to produce SCC by different tests as Slump flow, V-funnel flow and L-box test. All specimens were cured in water and the tests were carried out at different ages within the allowable limit provided by BS1881:1983.